The nutrional content of flamboyan leaves processed with different processing methods - Yelly Magdalena Mulik; Vivin Elmiyati Se'u; Basry Yadi Tang (Animal Husbandry Study Program, Faculty of Agriculture, Timor University, 2023)
Flamboyant (Delonix regia) is a plant that thrives all year round. This study aims to evaluate the nutritional content of flamboyant leaves processed with different processing methods. The study took in the Animal Feed Nutrition Laboratory of State Agricultural Polytechnic of Kupang from June to August 2022. The experimental design used was a Completely Randomized Design (CRD) with 5 treatments and 5 replications. The treatments tested were F1: flamboyant was dried in the shade for 5 days, F2: flamboyant was soaked in water for 4 hours, F3: flamboyant was soaked in a solution of rubbing ash for 4 hours, F4: flamboyant was ammoniated for 3 weeks, F5: flamboyant was fermented for 3 weeks. The results showed that the treatment tested had a very significant effect (P<0.01) on the content of organic matter, crude protein and crude fiber but had no effect (P>0.05) on the content of dry matter and crude fat. It can be concluded that the water immersion can increase the organic matter content, ammonia treatment increases the crude protein content and reduces the crude fiber content of flamboyant leaves.